2009
DOI: 10.3997/1873-0604.2009022
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing lakebed seepage and geologic heterogeneity using resistivity imaging and temperature measurements

Abstract: The contribution of groundwater-surface water exchange to lake budgets is poorly understood and depends in part on lakebed heterogeneities. These heterogeneities are difficult to characterize using traditional point sampling methods. The goal of this project was to use electrical resistivity to identify potential zones of groundwater discharge and recharge, providing focus for point measurements. Multiple resistivity surveys were conducted at Lake Lacawac, a small, glacially-formed lake in northeastern Pennsyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…ERT has been successfully used to investigate geologic features controlling seepage into lakes and rivers (Mitchell et al, 2008, Nyquist et al, 2009, contaminant seepage to a river (Slater et al, (Miller et al, 2008). To our knowledge, ERT has not been used to investigate hydrodynamics associated with RBF-related clogging.…”
Section: Methods For Monitoring Riverbed Clogging and Hydrological Rementioning
confidence: 99%
“…ERT has been successfully used to investigate geologic features controlling seepage into lakes and rivers (Mitchell et al, 2008, Nyquist et al, 2009, contaminant seepage to a river (Slater et al, (Miller et al, 2008). To our knowledge, ERT has not been used to investigate hydrodynamics associated with RBF-related clogging.…”
Section: Methods For Monitoring Riverbed Clogging and Hydrological Rementioning
confidence: 99%
“…Geophysical methods have been used in hydrologic characterization to avoid problems associated with point-source measurements by providing more detailed subsurface mapping ͑reviewed in Robinson et al, 2008͒. Geophysical applications in hydrologic studies include acoustic profiling ͑Cherkauer, 1991͒, radar ͑Day- Lewis et al, 2004͒, electromagnetic methods ͑Paillet et al, 1999Robinson et al, 2008͒, induced polarization ͑Titov et al, 2005͒, spontaneous potential ͑Nyquist and Corry, 2002͒, and resistivity ͑Belavel et al, 2003Manheim et al, 2004;Allen and Merrick, 2005;Day-Lewis et al, 2006;Mansoor and Slater, 2007;Swarzenski et al, 2007;Stieglitz et al, 2008;Nyquist et al, 2009͒. Resistivity, a measure of the resistance to electrical flow in a medium, is commonly used to locate and map contaminants and tracers in groundwater, to characterize groundwater flow through fractures, to determine the saltwater-freshwater interface in coastal areas, and to target zones of groundwater seepage ͑Cherkauer, 1991; Day-Lewis et al, 2006;Nyquist et al, 2008͒. Cherkauer ͑1991͒ uses a combination of marine resistivity surveys and seismic soundings to identify zones likely to have groundwater in-seepage in the river connecting Lake Huron and Lake Erie.…”
Section: Lakebed Characterizationmentioning
confidence: 99%
“…The effectiveness of ERT as a tool for assessing groundwater or surface water interactions within streams was investigated by Nyquist, Freyer and Toran (2008), who concluded that patterns of ground water discharge can be mapped at a detailed scale. Nyquist, Heaney and Toran (2009) concluded that towed resistivity is useful as a rapid reconnaissance tool for mapping geologic heterogeneity. The results can be used to position more time-consuming but higher-resolution lake-bottom resistivity measurements, which in turn can guide the placement a low-resistivity anomaly at vertical dike location to about 12 m below the sea bottom ( Figure 2b).…”
Section: Numerical Modelling and Data Inversionmentioning
confidence: 99%